Analyse des emplois non locatifs de BY - Lionel Dufaye (Anglophonia)
This article deals with the non-locative uses (be they spatial and temporal) of the preposition by. The first part is dedicated to the study of ‘qualifying values’ – i.e. any context where the by-PP qualifies either a distance or a relationship between two entities (e.g. I paid by check…, I did it step by step…). The second part deals with by in (so-called) ‘agent phrases’ in passives. This paper sets out to propose a unified explanation for both qualifying and passive uses. The working hypothesis assumes that by carries a differential value which qualifies a distance between two reference points. The values differ depending on the nature of the interval, which can be a route (I came here by bus), a gradual process (it grew hotter by the minute), a concurring process (I know some good music to cook by), any form of counter-expectation (I was late by 10 days), a change of state (as in passives)... In any case, by expresses discontinuity within a path-connected domain.